(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Since the beginning of human history, tuberculosis (TB) has threatened the wellbeing of mankind. The last Global Tuberculosis Report, published by the World Health Organization (WHO) in 2013, highlighted the significant burden in morbidity and mortality that Mycobacterium tuberculosis still bears in the world today [1]....